A single typical trichoscopic feature is predictive of tinea capitis: a prospective multicentre study. (29th April 2019) - Dhaille, F.; Dillies, A.‐S.; Dessirier, F.; Reygagne, P.; Diouf, M.; Baltazard, T.; Lombart, F.; Hébert, V.; Chopinaud, M.; Verneuil, L.; Becquart, C.; Delaporte, E.; et al.
Summary: Background: Specific trichoscopic signs of tinea capitis (TC) were first described in 2008. The accuracy of this diagnostic tool has not been evaluated. Objectives: To assess the diagnostic accuracy of trichoscopy. Methods: A prospective, multicentre study was done between March 2015 and March 2017 at the dermatology departments of four French university medical centres. Patients with a presumed diagnosis of TC were included. Trichoscopy was considered to be positive if at least one specific trichoscopic sign was observed. Trichoscopy results were compared with the gold standard for diagnosis of TC (mycological culture). Results: One hundred patients were included. Culture was positive for 53 patients and negative for 47. The sensitivity of trichoscopy was 94% [95% confidence interval (CI) 88–100], specificity was 83% (95% CI 72–94), positive predictive value was 92% and negative predictive value was 86%. Comma hairs, corkscrew hairs, zigzag hairs, Morse‐code‐like hairs and whitish sheath were significantly more frequent in patients with a positive mycological culture ( P < 0·001). Comma hairs were more frequent in patients with Trichophyton TC ( P = 0·026), and zigzag hairs were more frequent in patients with Microsporum TC ( P < 0·001). Morse‐code‐like hair was not observed in any patients with Trichophyton TC and therefore appears to be highly specific for Microsporum TC. Conclusions: The presence of a single trichoscopic finding is predictive of TC. Trichoscopy is a useful, rapid, painless, highly sensitive tool for the diagnosis of TC – even for dermoscopists with little experience of trichoscopy. It enhances physicians' ability to make treatment decisions. What's already known about this topic? Tinea capitis (TC) must be confirmed by a mycological culture that may take up to 6 weeks, delaying treatment. Specific trichoscopic signs of TC were first described in 2008, but the accuracy of trichoscopy for diagnosing TC has not previously been evaluated. What does this study add? The present series is the largest yet on the use of trichoscopy in the diagnosis of TC. Our results demonstrated that the presence of a single feature (comma hair, corkscrew hair, zigzag hair, Morse‐code‐like hair or whitish sheath) is predictive of TC. Trichoscopy is painless and highly sensitive. Morse‐code‐like hair appears to be highly specific for Microsporum TC. Abstract : Linked Comment: Brasileiro. Br J Dermatol 2019; 181 :893–894 . Plain language summary available online Respond to this article